The Utilization-Adjusted Output Gap : Is the Russian Economy Overheating? - Oomes, Nienke (IMF Working Papers; Working Paper, 2006)
This paper estimates the output gap in Russia using a utilization-adjusted production function approach, which we argue is preferable to traditional output gap methods. The approach amounts to (1) using available surveys to estimate the "natural rates" of capacity and labor utilization above which inflation begins to accelerate; (2) estimating a production function with utilization-adjusted capital and labor inputs; and (3) defining potential output as the level of output obtained when both capital and labor are at their estimated natural rates. The results suggest that the output gap in Russia was negative between 1999 and 2003, but may have recently become positive, thus contributing to inflationary pressures.